Proceedings of the First International Conference on Health, Social Sciences and Technology (ICoHSST 2020) 2021
DOI: 10.2991/assehr.k.210415.015
|View full text |Cite
|
Sign up to set email alerts
|

What Are the Facts in Online Nursing Education During the Covid-19 Pandemic?

Abstract: During the Covid-19 pandemic, there are a series of direct skills skills for nursing students. Changes in the learning force can have an impact on the faces of students and their learning achievements. However, the question of student olahihan problem in the way of isasi kecenyanyanya is still minimal. This research became the learning of psychomotor skills through online methods of student perspective. This qualitative research exists in a phenomenological way, which is capable of five student participants wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
1
0
1
Order By: Relevance
“…Changes in learning methods suddenly, so that lecturers and students try hard to learn the internet. There is concern that the achievement of learning objectives will not be optimal (Mediarti et al, 2021). The results of this study revealed that the learning outcomes of online method lectures were higher than those of the offline method.…”
Section: Discussionmentioning
confidence: 64%
“…Changes in learning methods suddenly, so that lecturers and students try hard to learn the internet. There is concern that the achievement of learning objectives will not be optimal (Mediarti et al, 2021). The results of this study revealed that the learning outcomes of online method lectures were higher than those of the offline method.…”
Section: Discussionmentioning
confidence: 64%
“…Peningkatan ketegangan di rumah sakit, stigma yang di labelkan oleh masyarakat kepada perawat, dan ketakutan penularan virus corona menjadikan kualitas kehidupan kerja perawat menurun. 2 Diharapkan institusi pendidikan dapat memberikan arahan pembelajaran khususnya di bidang manajemen keperawatan pada Quality of Nurse Work Life (QNWL) dan Turnover yang berguna untuk meningkatkan kualitas pendidikan perawat dalam menyiapkan calon perawat sebagai pengelola atau manajer. Hasil penelitian ini diharapakan kepada Institusi Rumah Sakit dapat menjadikan hasil penelitian sebagai solusi dalam pertimbangan pihak manajemen mutu pelayanan agar lebih memperhatikan kondisi perawat baik secara fisik dan psikis, terutama perawat yang mulai menunjukkan rasa tidak puas terhadap pekerjaan dan mencari tahu penyebab permasalahan untuk kemudian dapat di cari solusinya dengan cara membuka kotak saran atau saluran komunikasi kepada pihak manajemen.…”
Section: Kesimpulan Dan Saranunclassified